Predictors of institutionalisation in people with dementia. Issue 9 (21st August 2003) - Banerjee, S; Murray, J; Foley, B; Atkins, L; Schneider, J; Mann, A
Abstract : Objective: To identify what patient and carer characteristics influence transition into residential care for people with dementia. Method: Longitudinal study of a cohort of people with dementia and their carers in contact with old age psychiatric services in south London. Results: 100 people with dementia and their main family carer were recruited. At six month follow up 22 were in residential care, 63 in the community, 8 had died, and for 7 there were missing data. Between six and 12 months, 7 of the 63 in the community went into residential care, 4 died, and 12 were lost to follow up. The most striking finding is the 20-fold protective effect of having a co-resident carer (odds ratio 0.05, 95% confidence intervals 0.01 to 0.42, p=0.006). Higher ratings of behavioural problems in the person with dementia were also statistically significantly associated with transition into residential care as was the psychological domain of quality of life of the carer. Conclusion: These findings powerfully illustrate the pivotal role carried out by carers of people with dementia; interventions directly targeted at helping them to maintain this role would be supported by these data. These data also suggest that strategies directed at improving carer quality of life and at the resolution of behavioural disorder in the person with dementia may also have particular value.